Structures of Influence : A Comparative Approach to August Strindberg - Johns Blackwell, Marilyn; Johns Blackwell, Marilyn (Chapel Hill The University of North Carolina Press, 1981)
This collection of essays featuring contributions from eminent Swedish and American Strindberg scholars addresses the question of how Strindberg's art collides and colludes, ideologically and aesthetically, with the literary "doyens" of the nineteenth and twentieth centuries in both the Scandinavian and the larger Western cultural context.
National Endowment for the Humanities
Andrew W. Mellon Foundation
English
Keywords: Literature: history & criticism; German Studies; Literature